Drill on drill: adaptive oviposition strategies of Sycophila and Physothorax wasps on Ficus citrifolia - Oliveira Barros, Leví (2025)
Understanding tri-trophic interactions and the relationship among plants, herbivores, and their natural enemies is fundamental to advancing theoretical and practical ecology. Parasitoidism is among those interactions where tri-trophic levels are usually developed, with hyperparasitism and kleptoparasitism as examples. This study explores the interaction between fig wasps of the genera Physothorax Mayr, 1885 and Sycophila Walker, 1871 (Hymenoptera: Chalcidoidea) and the gall midge Ficiomyia brasiliensis Urso-Guimarães, 2024 (Diptera: Cecidomyiidae) associated with Ficus citrifolia Mill. in Ribeirão Preto, Brazil. Through behavioral observations and larval dissections we document the “drill on drill” strategy where Sycophila females utilize oviposition holes drilled by Physothorax females on the fig surface to access the host gall midge immatures. This behavior suggests a sophisticated adaptation for reducing oviposition time and conserving energy. Additionally, Sycophila behavior aligns with kleptoparasitic and hyperparasitic strategies, indicating a complex evolutionary history and ecological interaction. Our findings provide insight into the intricate relationships among non-pollinating fig wasps and their hosts, contributing to the broader understanding of tri-trophic interactions in fig microcosm.